Similarities and differences between the Arabic and Malay languages in constructing plurals: a contrastive analytical study - Sahlan, Siti Nur Fatihah; Alosman, Abdulrahman (KIRKHS, International Islamic University Malaysia, 2024)
Previous comparative studies have shown that there are similarities and differences in the construction of plurals between Arabic and other languages. The aim of this research is to identify the linguistic correspondence in constructing plurals between the Arabic language and the Malay language, and to point out the similarities and differences between the two languages in constructing plurals, while making a comparison between them through analyzing the differences between the two aforementioned languages. The researchers adopted the contrastive analysis approach in studying the plural structures between the Arabic and Malay languages, where they compared how the plurals are constructed withtextualanalysis in both languages. This comparative study resulted in a set of results, the most important of which are: the presence of special terms for plurals in both languages, and that the similarity in plurals is apparent between the two languages, as well as their differences, whether in nouns, numbers, or word repetition. The results also showed similarities and differences between plural structures in the two languages by analyzing the original text from Arabic and translating it into Malay